Arctic Zone of the North-Eastern region of Russia: problems of demographic development - Svetlana Sukneva (European Regional Science Association (ERSA), 2014)
The author describes the features of the demographic development of the Arctic zone of the North-Eastern region of Russia. The Arctic zone of the North-Eastern region of Russia is one of the most extreme regions of the world. Territories located after the Arctic a circle are included in the Arctic zone. Residence of people on this territory is attended with the whole complex of problems from which we will consider only demographic features. The Arctic zone of the North-Eastern region of Russia includes the Chukotka Autonomous District and half of the territory of the Republic of Sakha (Yakutia). The main reason of population reduction is migration. The population of the Arctic zone travels to places beyond the Northeast and to the central areas of the Republic of Sakha (Yakutia). Reproduction in the region shows a positive trend of natural increase. Relatively high birth rate remains due to higher reproductive attitudes of the rural population. Indigenous peoples of the North predominantly live in rural areas of the Arctic zone. Positive dynamics fertility has been accompanied by negative processes in the demographic behavior of the population. The Arctic areas have the highest rates of illegitimate births and celibacy among indigenous peoples of the Republic of Sakha (Yakutia). The adverse trends were observed in the mortality of the Arctic region. In Russia, in recent years, mortality rates are currently falling. The high mortality rate is observed in the Arctic zone. The reason for this situation is the high level of mortality from external causes, which is one and a half to two times higher than the average rate within the Russian Federation. The solution of the demographic problems is possible only in interaction with the economic policy of the state and the changing socio-economic situation in the Arctic zone. Priority directions to improve the demographic situation in the Arctic should be to reduce mortality and improve active healthy living, migration managements, strengthen the family and increase fertility in marriage. Demographic processes have considerable inertia, so to improve the demographic situation is necessary to preserve the demographic potential of the region and to eliminate the negative trends in demographic processes prevailing in the Arctic zone.
Keywords: J11; J19; R23; 330; Arctic zone of the North-Eastern region of Russia; region; demographic development; mortality; natural increase; migration